CRESCIMENTO DE Hymenaea courbaril EM AMBIENTES PROTEGIDOS E MATERIAL REFLETOR NA BANCADA DE CULTIVO - SOUZA, Vitória Cristina di Matheus e Souza; COSTA, Edilson; RODRIGUES, Carolina Garcia; SOUZA, Thulio Raphael Ferraz de (ANAIS DO ENIC, 2022)
-